Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di Gramedia Jambi - Deka Veronica; Ratih Rosita; Faradilla Herlin (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the effect of work discipline and work motivation on employee performance at Gramedia Jambi. The samples taken in this study were employees of Gramedia Jambi, totaling 38 respondents, drawn from 38 employees who have direct contact with consumers. The data collection techniques in this study used several techniques, namely library research and field studies consisting of interviews, observations and questionnaires. The analysis technique used is validity test, reliability test, classical assumption test, and hypothesis testing. The results showed that simultaneously the variables of work discipline and work motivation had a significant effect on employee performance, while partially work discipline had no significant effect on employee performance. Where the work motivation variable has a dominant influence on employee performance. Therefore, companies should maintain work motivation.